Cost-Benefit Analysis of Iceland's Search and Destroy Policy Against Methicillin-Resistant Staphylococcus aureus - Guðmundur I. Bergþórsson 1968- (2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of the bacteria Staphylococcus aureus (SA). Methicillin is an antibiotic that is effective in treating infection caused by SA but is ineffective in treating MRSA infection. The cost of treatment and the mortality rate of MRSA infection is estimated to be higher than another strain of SA, Methicillin-susceptible Staphylococcus aureus (MSSA). In Nordic Countries and the Netherlands, health care authorities employ a Search and Destroy Policy/Program (SDP) to hinder the spread of MRSA within hospitals. However, the actual benefit from the use of SDP is almost unknown. The aim of this study is to estimate the societal cost and benefit of the SDP applied against MRSA in Iceland. The research method involves calculations based on a hypothetical scenario model. The incremental benefit of the program and the cost for each year over 50 years are calculated then these amounts are discounted to estimate the present value of the program. In Iceland, the net social benefit (NSB) of the SDP is worth a total of ISK 833m. The NSB of each healthy and saved life year is worth ISK 0.5m, with the internal rate of return of the program at approximately 11% for the base case. Scenario analysis indicates that in order for the NSB to be positive the ratio of MRSA infections out of all SA infection needs to be higher than at least 17.5% and the mortality rate for MRSA infected patients needs to be at least 15.0% to 20.0% higher than the rate for MSSA infected patients. The results therefore indicate that the NSB of the Icelandic SDP is positive but is subject to differences in the consequences when compared to MSSA at a given level. Recommendations are made regarding the importance and validity of using cost-benefit methods to improve decisions and effective policies within the health care system.